3D printing applications in bone fabrication: a review - Evi J; Siska Oktaviyani; Mahjur Mahjur; Fitri Afriani (Gravity : Jurnal Ilmiah Penelitian dan Pembelajaran Fisika, 2021)
Bone scaffolding is an alternative solution to bone therapy, which is currently being developed in tissue engineering. This effort aims to produce a bone scaffold with a shape and specification according to bone therapy's needs. 3D printing is a scaffold fabrication method with promising prospects because it can produce scaffolding with physical characteristics as needed, both pore and physical. The method used in this article is a formal review to review various national and international literature using articles from 2000 to 2020 with the keywords "scaffold," "3D-printing", "bone," and "natural sources." The results of this article present various aspects regarding the use of 3D printing for scaffolding. Some aspects that are considered are how 3D printing works, the type of material used, and the scaffold's characteristics. It aims to get a clearer picture of the use of 3D printing, both its prospects/potential, application challenges, and future developments.